RA05.08: OPTIMAL RADIATION DOSE IN THE NEOADJUVANT TREATMENT OF ESOPHAGEAL CANCER: A COMPARATIVE EUROPEAN STUDY. (14th September 2018) - Mantziari, Styliani; Allemann, Pierre; Winiker, Michael; Messier, Marguerite; Demartines, Nicolas; Piessen, Guillaume; Schäfer, Markus
Abstract: Background: Current guidelines recommend the use of neoadjuvant chemo-radiation (NCR) for the treatment of locally advanced esophageal cancer, both types, adenocarcinoma (AC) and squamous cell carcinoma (SCC). So far, the optimal dose of radiotherapy to achieve a maximal tumor response within an acceptable toxicity is not yet determined. The aim of this study was to assess the impact of preoperative radiation dose on postoperative outcomes and long-term survival. Methods: Consecutive patients operated in two European tertiary centers for AC or SCC, treated with NCR and surgery from 2000–2016 were assessed. Specific postoperative complications (i.e. anastomotic leakage, atrial fibrillation), histological tumor regression grade (TRG, Mandard score), overall and disease-free survival were compared among three patients groups: group A (41.4Gy), group B (45Gy), and group C (50.4Gy). The x 2 or Fisher test were used for categorical variables and ANOVA for continuous variables. Survival analysis was done with the Kaplan-Meier method and log-rank test. Results: There were 294 patients included; 41.5% (n = 122) had AC and 58.5% (n = 172) SCC. Overall, 9.2%/27 patients received 41Gy, 57.8%/170 patients 45Gy and 33%/97 patients received 50.4Gy. Carboplatin-Paclitaxel was the most frequently used chemotherapy for group A (62.9%), and 5FU-Cisplatin for groups B (69.4%) and C (51.5%). Postoperative anastomotic leakage was lower for group B (7.1%) compared to group A (22.2%) and C (13.4%) ( P  = 0.036), as was the occurrence of atrial fibrillation (11.8% group B, 33.3% group A and 19.6% group C, P  = 0.013). Complete or excellent response (TRG 1–2) was significantly better for group B (58.2%), followed by group C (49.5%) and A (25.9%) patients ( P  = 0.012). Median overall survival was 48, 27 and 29 months for group A, B and C ( P  = 0.498), and median disease-free survival was 13, 27 and 18 months ( P  = 0.411), respectively. Conclusion: Preoperative radiotherapy dose of 45Gy with 5FU-Cisplatin was associated with a better histological response and less postoperative adverse outcomes compared to 41Gy and 50.4Gy, with no significant differences in long-term recurrence and survival. The role of the type of chemotherapy and histological tumor type are important co-factors affecting outcome and must be further assessed. Disclosure: All authors have declared no conflicts of interest.